2023
DOI: 10.3390/foods12051021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Probiotic Characteristics of Urolithin A Producing Enterococcus faecium FUA027

Abstract: Enterococcus faecium FUA027 transforms ellagic acid (EA) to urolithin A (UA), which makes it a potential application in the preparation of UA by industrial fermentation. Here, the genetic and probiotic characteristics of E. faecium FUA027 were evaluated through whole-genome sequence analysis and phenotypic assays. The chromosome size of this strain was 2,718,096 bp, with a GC content of 38.27%. The whole-genome analysis revealed that the genome contained 18 antibiotic resistance genes and seven putative virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A maximum concentration of 7.3 µmol/L of urolithin A was produced after 50 h of anaerobic culture in an ABB medium supplemented with 20 µmol/L EA and 0.005% L-cysteine. Other bacteria, such as Enterococcus faecium FUA029 and Lactococcus garviae FUA009, were also implicated in the production of urolithin A under similar growth conditions [31][32][33]. Urolithin A and B from EA were produced by Bifidobacterium pseudocatenulatum INIA P815 [34].…”
Section: Fermentation 0 H 24 H 48 H 72 H S Thermophilusmentioning
confidence: 99%
“…A maximum concentration of 7.3 µmol/L of urolithin A was produced after 50 h of anaerobic culture in an ABB medium supplemented with 20 µmol/L EA and 0.005% L-cysteine. Other bacteria, such as Enterococcus faecium FUA029 and Lactococcus garviae FUA009, were also implicated in the production of urolithin A under similar growth conditions [31][32][33]. Urolithin A and B from EA were produced by Bifidobacterium pseudocatenulatum INIA P815 [34].…”
Section: Fermentation 0 H 24 H 48 H 72 H S Thermophilusmentioning
confidence: 99%
“…Strains converting EA to Uro-A are currently limited. Bifidobacterium pseudocatenulatum INIA P815, Lactococcus garvieae FUA009, and Enterococcus faecium FUA027 isolated from human feces can produce Uro-A from EA Enterocloster bolteae CEBAS S4A9 isolated from human feces converted Uro-C to Uro-A .…”
Section: Introductionmentioning
confidence: 99%
“…Urolithins are produced in the gut following the microbiome-mediated transformation of the natural polyphenols ellagitannins (ETs) and ellagic acid (EA), which are present in dietary products, such as pomegranates, berries, and walnuts ( 15 25 ). Recently, in vitro culture studies have shown that Bifidobacterium pseudocatenulatum INIA P815 ( 26 ), Enterococcus faecium FUA027 ( 27 ), and Streptococcus thermophilus FUA329 ( 28 ) can metabolize ellagic acid to produce UroA. However, their role in UroA production in vivo has not yet been established.…”
Section: Introductionmentioning
confidence: 99%